DOSE ASSESSMENT FOR INTAKE OF TRITIATED WATER IN HUMANS: ROLE OF TRITIUM INCORPORATION IN ORGANIC MATTER - M. I. Balonov; L. A. Chipiga (Радиационная гигиена, 2017)
Tritium is one of the factors of internal exposure of the humans both in occupational and public environments. It enters the body mainly as tritiated water through inhalation, with food, drinks and through the skin; part of tritium gradually transforms into the metabolised organically bound tritium as a result of biochemical reactions. The purpose of this study was to evaluate organically bound tritium contribution to the effective dose of an adult using the biokinetic model and real dosimetric data. The data of long term monitoring from 6 studies with 17 workers or volunteers following single intake of tritiated water in the body were selected from 9 publications (1968-1997). Three two-compartment models of tritium biokinetics were used in this study: recurrent model with gradual transformation of tritium from tritiated water into organically bound tritium and tritiated water excretion; model with instant transformation of tritium into organically bound tritium and tritiated water excretion; model with instant transformation of tritium into organically bound tritium and both tritiated water and organically bound tritium excretion (according to ICRP). The ICRP model doesn’t properly reflect the real tritiated water metabolism in the human body: second exponent of the tritiated water content in the body water and accumulation of the organically bound tritium fraction are absent. The organically bound tritium fraction composes 3% of tritiated water in ICRP model. It is significantly higher compared to two other models (0,4% and 0,8%). According to the first model the contribution of OBT fraction to the mean dose varied from 1,8 to 4,6% for individuals; mean value was 3,0 ± 0,9%. According to the second model the contribution of organically bound tritium fraction was slightly higher: 3,6 ± 1,1%, according to the ICRP model – 9%. The dynamic of excretion of tritium with urine can be described with double-exponential curves and provides the basis for two-compartment modeling. The recurrent model with tritiated water excretion was more adjusted to human physiology. Contribution of organically bound tritium to effective dose can be somewhat higher than that to absorbed dose defined in this work. The presented dose assessment system can be used when specified individual absorbed dose reconstruction in tissues is necessary following accidental intake of large tritium activities.